2009
DOI: 10.1126/science.1174334
|View full text |Cite
|
Sign up to set email alerts
|

DICER1 Mutations in Familial Pleuropulmonary Blastoma

Abstract: A rare form of lung cancer in children is associated with mutational disruption of an enzyme that generates small noncoding RNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
480
2
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 621 publications
(504 citation statements)
references
References 6 publications
(6 reference statements)
11
480
2
11
Order By: Relevance
“…Initial clinical studies found that PPB and PPB-FTDS patients carry heterozygous DICER1 germline mutations and no homozygous loss of DICER1 was observed [6,33], which supported the DICER1 haplo-insufficiency hypothesis. However, this model was contradicted by recent studies showing that Dicer1-null cells (Kras G12D Trp53 −/ − Dicer1 −/ − ) from a mouse sarcoma cell line are competent for tumour formation, and that Pten/Dicer1 double-knockout mice develop primary fallopian tube tumours [17,34].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Initial clinical studies found that PPB and PPB-FTDS patients carry heterozygous DICER1 germline mutations and no homozygous loss of DICER1 was observed [6,33], which supported the DICER1 haplo-insufficiency hypothesis. However, this model was contradicted by recent studies showing that Dicer1-null cells (Kras G12D Trp53 −/ − Dicer1 −/ − ) from a mouse sarcoma cell line are competent for tumour formation, and that Pten/Dicer1 double-knockout mice develop primary fallopian tube tumours [17,34].…”
Section: Discussionmentioning
confidence: 85%
“…DICER1 germline mutations are known to predispose carriers to cancer [5], such as familial pleuropulmonary blastoma (PPB) [6]. Furthermore, heterozygous germline DICER1 mutations have been identified in PPB-related familial tumour-dysplasia syndrome (PPB-FTDS), multinodular goitre (MNG), Sertoli-Leydig cell tumour (SLCT), cystic nephroma (CN), Wilms' tumour, cervical embryonal rhabdomyosarcoma (cERM) and pineoblastoma [7][8][9][10].…”
Section: J Chen Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence, in fact, that specific miRNAs may be responsible at large for disease heterogeneity, functioning as regulators of tumorigenicity, invasion and metastasis (Tavazoie et al, 2008). Moreover, genetic defects in key components of the miRNA biosynthetic pathway have been described in tumors (Hill et al, 2009;Melo et al, 2009Melo et al, , 2010, and several genes involved in BC progression have been identified as targets of miRNAs that, in turn, are found deregulated in BC cells (Garzon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Initial wurde es aufgrund seiner Beschreibung im Kontext pleuropulmonaler Blastome und assoziierter Tumoren/Dysplasien [61] auch "pleuropulmonales Blastom, familiäres Tumor-und Dysplasie-Syndrom" genannt.…”
Section: Dicer1-syndromunclassified